Negative pressure wound therapy: eleven-year experience at a tertiary care hospital - Zargar, Haroon Rashid; Mohsin, Mir; Baba, Peerzada Umar Farooq; Wani, Adil Hafeez; Iqbal, Shabir; Zaroo, Mohammad Inam; Bashir, Sheikh Adil; Rasool, Altaf; Bijli, Akram Hussain; Bhat, Bashir Ahmed; Yasir, Mir (International Journal of Research in Medical Sciences, 2017)
Background: Management of complicated wounds is a reconstructive challenge. A reconstructive surgeon has to be ready to face new challenges every day. Negative pressure wound therapy has revolutionized the management of complex wounds. We are presenting our experience with this wound care modality in the past 11 years. Methods: It was a prospective study conducted from January 2006 to December 2016 on patients having wounds of varied etiologies, who consented to participate in this study. Custom made low cost NPWT was used till definitive wound closure. Results: A total of 568 patients consented to participate in the study during these 11 years. No major complications were seen. Most of these were males (60.73%) in their 3rd and 4th decade. Trauma was the leading cause of wounds in 38.14%, followed by diabetic foot wounds in 21.5%. Ankle and foot was the most common site of wounds (30.92%) followed by leg (24.01%). A total of 322 small, 218 medium and 97 large size dressings were used. Most of the patients improved with the NPWT. No major complications were seen. Conclusions: NPWT is safe, effective and has proved to be revolutionary in managing difficult wounds. With the use of customized low cost NPWT the benefit can be extended to underprivileged population in under developed nations too.